In vivo imaging reveals dendritic targeting of laminated afferents by zebrafish retinal ganglion cells - Mumm, Jeff S. (2006)
Targeting of axons and dendrites to particular synaptic laminae is an important mechanism by which precise patterns of neuronal connectivity are established. Although axons target specific laminae during development, dendritic lamination has been thought to occur largely by pruning of inappropriately placed arbors. We discovered by in vivo time-lapse imaging, that retinal ganglion cell (RGC) dendrites in zebrafish show growth patterns implicating dendritic targeting as a mechanism for contacting appropriate synaptic partners. Populations of RGCs labeled in transgenic animals establish distinct dendritic strata sequentially, predominantly from the inner to outer retina. Imaging individual cells over successive days confirmed that multistratified RGCs generate strata sequentially, each arbor elaborating within a specific lamina. Simultaneous imaging of RGCs and subpopulations of presynaptic amacrine interneurons revealed that RGC dendrites appear to target amacrine plexuses that had already laminated. Dendritic targeting of pre-patterned afferents may thus be a novel mechanism for establishing proper synaptic connectivity.